2019
DOI: 10.1002/jemt.23422
|View full text |Cite
|
Sign up to set email alerts
|

Digital light microscopy as a tool in toxicological evaluation of fish erythrocyte morphological abnormalities

Abstract: Fish erythrocytes are very sensitive to environmental pollution because they exhibit pathological alterations before appearance of other external symptoms, may be used as reliable toxicity bioindicators. Microscopic analysis can be a useful tool in early detection of alterations in erythrocyte morphology due to different environmental stressors, and in predicting organism's possible response ways. This study aims to evaluate the toxicity of a polluted freshwater lake on the erythrocytes of crucian carp fish, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…In general, haematology is an important tool to evaluate the fish health in relation to diseases, stress, nutrition and changes in environmental conditions (Burgos‐Aceves et al, 2019; Enayat Gholampour et al, 2020; Fazio, 2019; Ghafarifarsani, Hoseinifar, Aftabgard, et al, 2022; Rashidian, Kajbaf, et al, 2020; Sula et al, 2020). In this study, dietary DKE caused significant increases in the values of Hct, RBCs, MCV, Hb content and MCHC.…”
Section: Discussionmentioning
confidence: 99%
“…In general, haematology is an important tool to evaluate the fish health in relation to diseases, stress, nutrition and changes in environmental conditions (Burgos‐Aceves et al, 2019; Enayat Gholampour et al, 2020; Fazio, 2019; Ghafarifarsani, Hoseinifar, Aftabgard, et al, 2022; Rashidian, Kajbaf, et al, 2020; Sula et al, 2020). In this study, dietary DKE caused significant increases in the values of Hct, RBCs, MCV, Hb content and MCHC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure concentration showed a strong positive correlation with HSI and TSG, indicating that the values of these parameters increased from control to the highest exposure concentration. While toxicology studies have demonstrated the disruptive effects of pesticides on erythropoietic tissues [89][90][91][92][93], the relatively higher sensitivity of MCH compared to other hematological parameters in fish at elevated toxicant exposure concentrations have been reported [94]. The significant reduction in MCH across exposure groups (p < 0.05) when compared with the control could be attributed to lowered levels of cellular blood iron or heme-synthesis dysfunction, which stresses the fish by reducing the oxygen-carrying capacity of its blood [89,95].…”
Section: Correlation Analysismentioning
confidence: 99%
“…Accordingly, the erythrocytes in target organs offer a unique tool for assessing the cytotoxicity in fish (Fazio, 2019 ; Soliman and Sayed, 2020 ). Eryptosis and erythron profiles (poikilocytosis and nuclear abnormalities) of fish erythrocytes are valuable biomarkers of the toxicity of different chemicals, pharmaceutical residues, and ultraviolet radiation (Mekkawy et al, 2011 ; Morina et al, 2012 ; Sayed et al, 2013 , 2015 , 2016 , 2017 ; Sayed, 2016 ; Sula et al, 2020 ). The internal health conditions of the fish can be classified according to the indices iterating serum biochemical, hematological, and immunological aspects (Edsall, 1999 ; Luskova et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%